Quantifying internal and external training loads in professional ballet dancers: the role of session type and sex - Brogden, C.; Brown, M.; Jones, A.; Travis, E.; Potts, D.; Till, K.; Weaving, D.; Schofield, C.; Wild, S. (International Journal of Sports Physiology and Performance, 2026)
Purpose: To (1) quantify the internal and external training-load (TL) demands of professional ballet dancers and (2) explore the influence of session type and sex on TL. Methods: Twenty-nine professional ballet dancers (men = 14, women = 15) were monitored over 2 weeks. Internal TL data were measured using heart rate (HR) -derived training impulse (TRIMP) and external TL using PlayerLoad (PL). TL data from 303 sessions were categorized and analyzed according to session type (rehearsal, class, and conditioning) and sex. Results: Dancers averaged ~4.62 h/d (~26.1 h/wk) comprising daily (PL: 539 arbitrary units [AU], HR TRIMP: 314 AU) and weekly (PL: 2608 AU, HR TRIMP: 1503 AU) TL. Rehearsals had the longest duration (197 [66] min) but lowest load per minute. Conditioning produced the highest PL (140.1 AU; 95% CI, 120.2-160.0), while class elicited the greatest HR TRIMP (89.4 AU; 95% CI, 72.1-106.7). Session type significantly influenced TL (P = .004, Eta2 = .68), with small to moderate differences between rehearsal and conditioning (PL effect size = 0.38, TRIMP effect size = 0.49). No significant differences were observed by sex (PL, P = .57; TRIMP, P = .18). Conclusions: Conditioning sessions produced the greatest TL response and should play a key role in professional ballet dancers` schedules. Although TL did not significantly differ by sex, the study suggests that a uniform training model may not meet individual dancer needs. These findings support the implementation of personalized monitoring and periodized scheduling strategies to optimize both artistic and physical performance in professional ballet.